Legal Review of the Security of Anarchist Demonstrations by the Indonesian Police Mobile Brigade Corps (Study of Security for the 2024 Pilkada Demonstrations in Semarang City by Batalyon A Pelopor Sat Brimob Polda Jateng) - Sukirno, Sukirno; Arpangi, Arpangi (UNISSULA Semarang, 2025)
Abstract. Freedom of speech is important in a democratic country, including Indonesia. The government has guaranteed freedom of speech by issuing a number of laws and regulations as its legal umbrella. One of the human rights guaranteed by the state is expressing opinions. The article on freedom of speech is regulated in the 1945 Constitution, Article 28F. Article 28E paragraph (3) of the 1945 Constitution states that everyone has the right to freedom of association, assembly, and expression of opinion. The 1945 Constitution of the Republic of Indonesia guarantees demonstrations in the form of free parades and pulpits and all the basic principles of organizing state life, therefore including them as constitutional rights, to protect, fulfill and promote them. Police members in carrying out their roles and functions cannot be separated from very basic rights such as human rights in general. There have even been plans to revise the TNI/POLRI Law to further strengthen the dual function that was once used by the New Order government as a tool to perpetuate power for 32 years and the Government at that time wanted to make the New Order government period with different methods but the same goals, so that it gives the impression that Jokowi is a neo-New Order leader which means a New Order style with more mature maneuvers and also updating methods for the succession of power and his cronies are the same as the New Order era. Regarding the demonstration by BEM Semarang Raya, Cipayung Plus Semarang City Civil Society Network and the People's Movement to Sue regarding the Pilkada Bill in front of the Semarang City Hall Office. On Monday, August 26, 2024 at 15.11 to 18.30 WIB in front of the Semarang City Hall Office, Jl. Pemuda, Sekayu Village, Semarang, a demonstration was held by BEM Semarang Raya, Cipayung Plus Semarang City Civil Society Network and the People's Movement to Sue regarding the Pilkada Bill Coordinator Mr. SA'AD (UIN Walisongo Semarang) and Mr. RIKI (UNISULA Semarang) Sandra Marjuki.